Characterization of decellularized ovine small intestine submucosal layer as extracellular matrix‐based scaffold for tissue engineering. Issue 3 (22nd April 2017) - Rashtbar, Morteza; Hadjati, Jamshid; Ai, Jafar; Jahanzad, Issa; Azami, Mahmoud; Shirian, Sadegh; Ebrahimi‐Barough, Somayeh; Sadroddiny, Esmaeil
Abstract: Extracellular matrix‐based scaffolds derived from mammalian tissues have been used in tissue engineering applications. Among all the tissues, decellularized small intestine submucosal layer (SIS) has been recently investigated for its exceptional characteristics and biocompatibilities. These investigations have been mainly focused on the decellularized porcine SIS; however, there has not been any report on ovine SIS (OSIS) layer. In this study, OSIS was decellularized and its physical, chemical, and morphological properties were evaluated. Decellularization was carried out using chemical reagents and various physical conditions. The effects of different conditions were evaluated on histological and biomechanical properties, quality of residual DNA, GAPDH gene expression, and biocompatibility. Results revealed satisfactory decellularization of OSIS which could be due to its thin thickness. Mechanical properties, structural form, and glycosaminoglycan contents were preserved in all the decellularized groups. In SDS‐treated groups, further cells and DNA residues were removed compared to the groups treated with Triton X‐100 only. No toxicity was observed in all treatments, and viability, expansion, and cell proliferation were supported. In conclusion, our results suggest that OSIS decellularized scaffold could be considered as an appropriate biological scaffold for tissue engineering applications. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 933–944, 2018.